Inequality in China : Trends, Drivers and Policy Remedies - Jain-Chandra, Sonali (IMF Working Papers; Working Paper, 2018)
China has experienced rapid economic growth over the past two decades and is on the brink of eradicating poverty. However, income inequality increased sharply from the early 1980s and rendered China among the most unequal countries in the world. This trend has started to reverse as China has experienced a modest decline in inequality since 2008. This paper identifies various drivers behind these trends - including structural changes such as urbanization and aging and, more recently, policy initiatives to combat it. It finds that policies will need to play an important role in curbing inequality in the future, as projected structural trends will put further strain on equity considerations. In particular, fiscal policy reforms have the potential to enhance inclusiveness and equity, both on the tax and expenditure side.